The Evolving Brain: Unraveling the Forces Shaping Human Cognition - R. Tjandrawinata, Raymond (Asian Journal of Social and Humanities, 2025)
This interdisciplinary study explores the evolution of the human brain by integrating perspectives from anthropology, neuroscience, evolutionary biology, and technology studies. It delves into the factors driving brain expansion over time, including social complexity, dietary transitions, tool use, and the development of language. By synthesizing primary and secondary data, the research highlights the interplay between cognitive development and environmental pressures, showcasing how human neural architecture was shaped by adaptive responses to changing conditions. The findings reveal that evolutionary adaptations not only influenced brain size and structure but also laid the groundwork for cognitive resilience, particularly in the face of aging and modern technological advancements. This study underscores the profound impact of social and environmental challenges on brain evolution and its ongoing plasticity. Furthermore, it addresses critical questions about how rapid technological shifts are shaping cognitive functions and neural pathways today. By examining the past, present, and future trajectories of the human brain, this research provides a comprehensive framework for understanding its evolutionary processes and offers insights into navigating the challenges of an increasingly complex and technology-driven world.